Spiders indicate delivery of an agri-environment scheme at multiple diversity levels - Jeanneret, Philippe; Pozzi, Stefano; Martinez Nuñez, Carlos (Frontiers in Ecology and Evolution, 2022)
Agri-environment schemes (AES) are expected to counteract the negative impacts of intensive agriculture on biodiversity. These schemes were specifically designed to target farmland biodiversity and included, for instance, ecological focus areas (EFAs). In Switzerland, in order to qualify for direct payments, farmers must manage 7% or more of their land as biodiversity promotion areas (BPAs). BPAs encompass extensively managed and low intensity hay meadows, fallows (wildflower strips), traditional orchards with high-stem trees and hedgerows. Evaluation of AES delivery for biodiversity is of crucial importance but must be performed across several years and considering the various components of species diversity to avoid incomplete or wrong conclusions. From a complex study design 7comprising 478 fields in three regions and four sampling years, spider assemblages of BPA habitats were compared to corresponding conventionally managed fields. A battery of investigations was performed including alpha- and beta-diversity analysis, multivariate dispersion, indicator species and species specificity to understand what BPAs deliver for spiders in the habitat scale and farming landscape. Results showed that alpha-diversity (average number of species) was usually higher in BPA habitats than in conventionally managed fields but the species composition (beta-diversity) had more power to perceive AES impact. Furthermore, the various environmental conditions of BPAs in the farming landscape led to highly diverse spider assemblages (multivariate dispersion) emphasizing that not only the agricultural management plays a role in determining species diversity but the environmental heterogeneity. Indicator (and rare) species were mostly found in woody BPAs (hedges and high-stem tree orchards) revealing the high importance of these BPA habitats for spider conservation. At regional scale, BPA hedges contributed most to the regional diversity of spiders in grassland and mixed regions while BPA meadows and wildflower strip BPAs were first delivering in the region of arable crops. Recommendations highlight the role of the woody habitats and of the environmental heterogeneity in the farming landscape as well as of regional planning to make AES effective.